Case report: Fibromatosis colli in a neonate - Smiti S; Kulkarni Naveen; Singh Jyoti (Indian Journal of Radiology and Imaging, 2010)
Fibromatosis colli or pseudotumor of infancy of the sternocleidomastoid muscle is a rare cause of a benign neck mass in neonates and infants. If diagnosed correctly, it can be managed conservatively, and unnecessary investigations can be avoided.